PENERAPAN MODEL LATIHAN SHOOTING FUTSAL PADA EKSTRAKURIKULER SMK AMAL BAKTI JATIMULYO - Diki Pramono; Imam Mahfud (Universitas Teknokrat Indonesia, 2022)
The purpose of this study was to determine whether or not there was an effect of the futsal shooting practice model on the accuracy of futsal shooting at the extracurricular activities of SMK Amal Bakti Jatimulyo. The population used in this study were all students who took part in futsal extracurricular at SMK Amal Bakti Jatimulyo and the sample in this study was 20 male students as the experimental class. With exercises carried out for one and a half months with 16 meetings, as well as variations of exercises combined with basic techniques and futsal ball formations, so that students do not experience boredom.Based on the results of data analysis, description, research results, and discussion conclusions can be drawn, namely: From the results of the t test it can be observed that t count is greater than t table (20.375) (1.729) and a significant value of p is (0.000 0.05), These results explain that there is a significant difference between the pretest and posttest of the futsal shooting exercise model in the extracurricular activities of SMK Amal Bakti Jatimulyo. The average pretest data is 19.35 while the posttest is 24.65 with an increase of 5.3.